Recurrent splenic volvulus after splenopexy in an 11-year-old child: A case report - Christelle Sommer; Paola Andrea Rouge Elton; Nermin Halkic; Meriam Koob; Leonor Alamo; Sylvain Mauron; Eleuthere Stathopoulos (Elsevier, 2024)
Introduction: Recurrence of splenic volvulus after splenopexy in children is rare. A consensus on the optimal surgical strategy in splenic volvulus is lacking. Case Presentation: An 11-year-old female presented left upper quadrant abdominal pain for 24 hours following a short-lived appearance of an epigastric bulge. A CT-scan demonstrated findings consistent with splenic volvulus, without distal arterial flow. She underwent an exploratory laparoscopy, splenic detorsion, and splenopexy to the abdominal wall using two non-resorbable, knotless, unidirectional barbed sutures. The patient was discharged on day 2 after the procedure. A 6-month follow-up ultrasound showed a normally perfused spleen. Then months after the operation she presented with the same abdominal symptoms. A CT scan confirmed the recurrence of the splenic volvulus. She underwent a second laparoscopy, splenic detorsion, and splenopexy with a tailor-made mesh bag anchored to the abdominal wall. She recovered well from that operation. At 10 months of follow up she has had no recurrent of symptoms and the spleen is well vascularized by ultrasound. Conclusion: Simple splenopexy using direct sutures to abdominal wall may not be sufficient to create adequate adhesions and prevent recurrence. The use of a mesh may have a higher success rate.